Analisis Kemampuan Siswa pada Penilaian Sumatif Mata Pelajaran Kewarganegaraan - Iriyani, Sri Astuti (Varied Knowledge Journal, 2024)
This study aims to analyze the skills of students in the end-of-semester assessment in the subject of Civic Education (PKN). The research method applied is quantitative descriptive research using data from the odd semester exam results for the 2023/2024 school year as the material for analysis. The research sample consisted of 31 fourth grade elementary school students in Jayapura city. Data was collected through document analysis and direct observation of the assessment process. The results showed that 78% of the learners achieved good assessment. Factors that influenced learners' skills included teaching methods, learning environment support, and learners' interest in the subject. The implications of the findings emphasize the importance of developing inclusive and adaptive evaluation strategies, as well as improving the effectiveness of teaching methods to ensure optimal learning achievement in Civics.